The Effect of Brand And Price on Mineral Water Purchase Decision (The Study of Semongkat Brand Local Gallon Mineral Water in Sumbawa District) - Indra Kusumawati (Institute of Computer Science (IOCS), 2021)
Sumbawa Regency is a district in the Province of West Nusa Tenggara (NTB) Indonesia, where there are lots of local products, one of which is Semongkat Brand Gallon drinking water. Taken from natural springs from the mountains of Semongkat Tourism Village, Sumbawa Besar. The Objective is to significantly determine the effect of variables between brands and prices to the consumer’s decision in doing repurchased gallons of Semongkat mineral water in Sumbawa Regency. To find out which variables have the most significant influence on consumer decisions in repurchasing gallons of mineral water from the Semongkat brand in Sumbawa Regency, the type of research used is the associative one, which is a form of research aims to determine the relationship between two or more variables. This research builds a theory that can function to explain, predict and control a symptom. The population in this study are buyers (housewives) who make the decision to repurchase Semongkat brand mineral water products with the choice of gallon water. The sampling technique used was quota sampling technique based on certain considerations from the researcher (Djarwanto et.all, 1993:119) . For the number of population p is not known with certainty. The number of samples to be studied is 30 people. The variables of this research are the brand (X 1 ), the price is (X 2 ) and the purchase decision is (Y) and therefore, data collection method used should be the method of random sampling, While the data collection technique should use a questionnaire. The analytical tools used in this research are Multiple Linear Regression Test and Statistical Test. The findings of this study are partial and simultaneous findings. There is an influence between the variables brand, price, on the decision to purchase gallon water from the Semongkat brand in Sumbawa Regency .